Pengembangan Modul Pembelajaran Menulis Teks Cerpen Berbantuan Gambar Berseri untuk Meningkatkan HOTS Siswa Kelas XI SMK YASPI Labuhan Deli - Sari, Nilam; Rita, Rita; Safina, Nila; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aimed to develop and assess the feasibility of a learning module for short story writing using picture series media to enhance higher-order thinking skills (HOTS) in Class XI of SMK Yaspi Labuhan Deli. The research and development approach was employed, following the 4-D development model by Thiagarajan (1974): definition, design, development, and deployment. The population consisted of 193 students, with a sample size of 30 students. The results demonstrated that the developed learning module met the criteria effectively. The assessment of validity by material experts yielded a percentage value of 78% (good category), and by design experts, it was 95% (very good category). Teachers' assessment of feasibility resulted in 80% (good category), and students' limited trial received 88% (very good category). In conclusion, the learning module for short story writing with picture series media is valid and suitable for implementation as a teaching resource to enhance HOTS in Class XI of SMK Yaspi Labuhan Deli.